EFFECTIVE STRATEGIES FOR TEACHING SYNONYMS AND ANTONYMS TO 6 TH GRADE LEARNERS OF ENGLISH - Xaydarova Shoira; Anorboyeva Oydinoy Azizbek qizi (TADQIQOTLAR, 2026)
Abstract: This work explores effective strategies for teaching synonyms and antonyms to 6th grade learners of English. The approach emphasizes the use of context clues, word maps, and matching games to help learners differentiate meanings and understand usage variations. Teachers guide students in recognizing subtle differences between words, supporting deeper semantic awareness. Activities such as sentence creation enhance learners’ ability to apply new vocabulary in both spoken and written communication. The use of thesaurus exploration and word families further expands students’ vocabulary knowledge and promotes independent learning. Continuous repetition, practice, and integration of real-life examples ensure retention and appropriate usage of synonyms and antonyms. Overall, these strategies create an interactive and meaningful learning environment that strengthens vocabulary development among 6th grade English learners.